English Lexical Items of Arabic Origin: A Linguistic Study - Al-Sabaee, Khalid Ali Youssif; Mohdar , Awatif Saleh Ali (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study is a linguistic one. It investigates the English words of Arabic origin. These borrowed words are organized and classified into different groups with their percentages. Sound modification of these words are also taken into consideration for the Arabic words to be nativized in English. It is clear that English borrowed various lexical items from many languages and Arabic is one of them. These words are classified into different groups: words related to animals, words related to vegetables, Fruit and food, words related to perfume, words related to science, words related to Islamic religion and miscellaneous words. However, borrowing is a linguistic phenomenon that no language can escape from it. This study comprises seventeen sections, they are as following an abstract, an introduction, objective of the study, significance of the study, limitation of the study, data collection, methodology, language, word – formation processes, borrowing phenomenon, types of borrowing, causes of borrowing, English language and the Arabic lexical items, data analysis, phonological changes, conclusion and references.